The oxford companion to english language - McArthur, Tom [ed.] (Oxford Oxford University Press, 1992)
This language reference book, written by over 90 specialist contributors, contains articles ranging from the "core" aspects of English - its grammar, history, pronunciation and usage - to such wider issues as linguistics, education, literature, technology and geography. There are entries for people, books and institutions which have shaped the language, or its study, and there is wide coverage of english throughout the world, and the influence of politics and culture. Fully cross-referenced with bibliographies for major entries, and an index of people included in the text, the volume also contains a chronology of the english language from Roman times to the 1990s.
Keywords: English language